Creation of environmental monitoring computer system - Rahimova Nazila Ali,; , Abdullayev Vugar Hacimahmud; Abbasova Vasila Soltanaga, (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Abstract: The object of the research is environmental monitoring. This article describes environmental monitoring. It also addresses the purpose, functions and main issues addressed by the environmental monitoring system. This article focuses on environmental protection. With the help of an environmental monitoring system, it is possible to forecast the future level of environmental pollution. The environmental monitoring system is part of the environmental information system. This article also discusses the main components, functions, objectives and objectives of environmental information systems. It also describes the knowledge base, which is part of the environmental information system. One of the problems is the systematization of environmental data. Relational tables were used in the research. The research looked at an environmental information system that uses to manipulate environmental data. Part of this system is environmental monitoring, which is used to monitor the environment. The main part of the environmental information system is a database in which all necessary information is structured. This article discusses the main issues to be addressed in the environmental information system. Requirements for such a system are also considered. The structure of the environmental information system consists of three levels: high, medium, low. This article also discusses the conceptual model and structure of the database. The article has developed an information system that addresses various issues in the environmental monitoring system, such as atmospheric air and precipitation, water, soil pollution levels, as well as the cost of radioactivity. In addition, the IS makes the appropriate calculations for these components and presenting their results in various forms and etc. The results of this study will provide a more detailed description of the level of environmental pollution, i.e. improve environmental monitoring.